Extremely Acidic Soils are Dominated by Species-Poor and Highly Specific Fungal Communities - Hujslová, Martina; Kubátová, Alena; Bukovská, Petra; Chudíčková, Milada; Kolařík, Miroslav (Microbial ecology, 2017)
Highly acidic soils (pH < 3) represent an environment which might potentially offer new biotechnologically interesting fungi. Nevertheless, only little data on fungal communities in highly acidic habitats are available. Here, we focused on the diversity of cultivable filamentous microfungi in highly acidic soils (pH < 3) in the Czech Republic. Altogether, 16 soil samples were collected from four sampling sites and were processed by various approaches. In total, 54 fungal taxa were isolated and identified using classical as well as molecular markers. All dominant species were found both as living mycelia and as resistant stages. Numerous recently described or unknown taxa were isolated. The core of the fungal assemblage under study consisted of phylogenetically unrelated and often globally distributed fungi exclusively inhabiting highly acidic habitats like Acidiella bohemica, Acidomyces acidophilus, and unidentified helotialean fungus, as well as taxa known from less acidic and often extreme environments like Acidea extrema, Penicillium simplicissimum s.l., and Penicillium spinulosum. The large number of identified specialized species indicates that highly acidic environments provide suitable conditions for the evolution of specialist species. The occurrence of ubiquitous fungi in highly acidic substrates points to the principal role of competition in the colonization of such environments. The detected taxa did not require low pH to survive, because they can grow in a broad range of pH.
Keywords: houby; Ascomycota; Soil Microbiology; Microscopic fungi; ekosystém; Acidea; klasifikace; biodiverzita; Penicillium; koncentrace vodíkových iontů; DNA fungální; Česká republika; Classification; Czech Republic; Fungi; Base Sequence; sekvence nukleotidů; Acidomyces; Hydrogen-Ion Concentration; půdní mikrobiologie; Soil; fylogeneze; DNA, Fungal; Species Specificity; Biodiversity; Diversity; Acidiella; Acidohtrix; kyseliny; druhová specificita; Acids; Ecosystem; Phylogeny; půda